Health and safety management : principles and best practice - Fuller, Colin; Vassie, Luise H. (Harlow, England ; New York : Prentice Hall/Financial Times, 2004)
This book places the theory and practice of occupational health and safety firmly within a strategic business context by making health safety an equal partner to other strategic business risks.
Includes bibliographical references and index.
oif 13/03/15
Loan
Keywords: Hospitals -- Risk management; Risk assessment